Is the Imitative Competence an Asymmetrically Distributed Function? - Fabri, Mara; Pierpaoli, Chiara; Foschi, Nicoletta; Polonara, Gabriele (Frontiers in Systems Neuroscience, 2021)
The present article reconsiders behavioural and functional data from studies investigating the anatomical imitation and the related mental rotation competence, carried out by our group in healthy subjects, with intact interhemispheric connections, and in split-brain patients, completely or partially lacking callosal connections. The results strongly point to the conclusion that anatomical imitation and mental rotation competences require interhemispheric communication, mainly occuring through the corpus callosum, which is the largest white matter structure in the human brain. The results are discussed in light of previous studies and of future implications.